Anaesthesia for ruptured ectopic pregnancy at district level - David G. Bishop; Simon P.D.P. le Roux (South African Family Practice)
In South Africa, deaths as a result of ectopic pregnancies are increasing despite the overall improvements in maternal mortality. These deaths occur predominantly in district hospitals, with the final cause of death being hypovolaemic shock in almost all cases. In most cases, no anaesthesia was attempted despite the district hospitals having the clinical skills, equipment and infrastructure to provide a caesarean delivery service. It appears that there is a skills gap between the provision of anaesthesia for caesarean delivery and that of ruptured ectopic pregnancy. There is a growing recognition of the urgent need to prioritise the provision of emergency surgical care in rural settings. This should be viewed not as a luxury but as an absolute necessity. In this study, we aim to discuss the pathophysiology of a patient with a ruptured ectopic pregnancy briefly, outline district hospital requirements for safe surgery and then discuss a simple, safe method for the provision of anaesthesia in patients deemed too unstable to transfer to a referral facility.